The quantum harmonic oscillator expected shortfall model - Markovic, Vladimir M.; Radivojevic, Nikola; Ivanovic, Tatjana; Radisic, Slobodan; Novakovic, Nenad (Estudios de Economía, 2024)
This paper presents a new Expected Shortfall (ES) model based on the Quantum Harmonic Oscillator (QHO). It is used to estimate market risk in banks and other financial institutions according to Basel III standard. Predictions of the model agree with the empirical data which displays deviations from normality. Using backtesting, it is shown that the model can be reliably used to assess market risk.